Orthopedic manual therapy assessment and management - Schomacher, Jochen (Thieme, 2014)
"Orthopedic Manual Therapy presents a systematic, step-by-step guide to manual therapy for disorders of the extremities and spine. Readers will find detailed examination and treatment techniques, the newest scientific and clinical advances, and updates on pain physiology, biomechanics, neurodynamics, and the biopsychosocial model of disease as the foundation for manual therapy"--Publisher's website